A qualitative study examining psychosocial distress and coping mechanisms among orphan and vulnerable children living in institutional care in New Delhi, India - Abhishek Saraswat; Sayeed Unisa (Journal of Health and Social Sciences)
Introduction: India is home to the largest population of orphaned children in the South Asia, who are at increased risk of poor psychosocial well-being. In the Indian context, literature on the psychosocial well-being of orphans and vulnerable children (OVC) is scarce. Our research was aimed at fulfilling this gap by understanding self-reported psychosocial distress among OVC and subsequent coping strategies adopted during their stay at orphanages. Methods: The present study was conducted in three randomly selected orphanages of Delhi, India, during August-December 2016. Fifteen children (M = 9, F = 6) aged 10-17, were selected for in-depth interviews through a non-probability purposive sampling. Descriptive analysis was used to describe the characteristics of the study participants. Data analysis required the examination and comparison of interview transcripts for content analysis and themes identification. Results and Discussion: Our findings revealed psychological turmoil and poor social cognition among OVC. Even though children were happy to enjoy their basic necessities of life, the majority of them faced parental bereavement yearning for love, and desiring advocacy and guidance in life. OVC showed low self-concept and lack of purpose in life. Isolation from outside world resulted in feelings of mistrust among OVC. They also felt stigmatized, socially excluded and remained distressed. Coping strategies adopted by OVC included praying to God, forgetting parents, shifting focus, avoiding crowded places, and treating inmates as their family. They also reported indulgence in self-discrimination, substance abuse, and delinquency to avoid psychosocial distress. Conclusions: Ongoing programs aimed exclusively at fulfilling materialistic needs of OVC could lose focus on their psychosocial issues. New robust interventions are required not only for sufficing the quality services, but also for identifying psychological issues, enhancing social skills, and improving coping strategies and building resilience among OVC.